2015
DOI: 10.1186/s12879-015-1278-0
|View full text |Cite
|
Sign up to set email alerts
|

Health care workers in Pearl River Delta Area of China are not vaccinated adequately against hepatitis B: a retrospective cohort study

Abstract: BackgroundsHealth-care workers’ (HCWs) exposure to bodily fluids puts them at risk of hepatitis B virus HBV infection. This study investigated HBV vaccination practices and outcomes in HCWs and assessed postvaccination seroprotection across HCWs in different departments.MethodsA survey of HCWs in a Chinese public general hospital was carried out with a retrospective cohort of 1420 hospital HCWs (458 males and 962 females). HBV vaccination status (10-μg/dose used) was investigated in the cohort from vaccination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…This phenomenon was partly due to a lack of ideological understanding and shared expertise. A retrospective cohort of 1420 HCWs, studied in the Pearl River Delta Area of China, showed that the overall vaccination rate among HCWs was 40.42% (574/1420), which was disappointingly low . ID medical staff had higher vaccination rates (57.8%) compared to the noninfectious disease staff (39.1%).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was partly due to a lack of ideological understanding and shared expertise. A retrospective cohort of 1420 HCWs, studied in the Pearl River Delta Area of China, showed that the overall vaccination rate among HCWs was 40.42% (574/1420), which was disappointingly low . ID medical staff had higher vaccination rates (57.8%) compared to the noninfectious disease staff (39.1%).…”
Section: Discussionmentioning
confidence: 99%
“…The acquired data indicate that the protection efficiency ranges between 64% (Catalonia) and 83% (Japan), i.e. these are the percentages of examinees with protective anti HBs antibodies [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…The YRD plays a leading role in Chinese economic growth, and considerable energy is needed for economic growth and social development [62]. The main industries of the YRD include electronic equipment manufacturing, transportation equipment manufacturing, electricity supply, ferrous metal smelting and processing, chemical materials and products manufacturing, and light industry such as the textile industry [63]. With flourishing tertiary industries and high-tech secondary industries, the ecological and environmental condition is better than that in BTH.…”
Section: Discussionmentioning
confidence: 99%